Unit‐cell response of tetragonal hen egg white lysozyme upon controlled relative humidity variation. Issue 4 (24th July 2019) - Logotheti, S.; Valmas, A.; Trampari, S.; Fili, S.; Saslis, S.; Spiliopoulou, M.; Beckers, D.; Degen, T.; Nénert, G.; Fitch, A. N.; Karavassili, F.; Margiolaki, I.
Abstract : The effects of relative humidity on a tetragonal crystal form of hen egg white lysozyme are studied via in situ laboratory X‐ray powder diffraction. Abstract : Variation of relative humidity (rH) greatly affects the internal order of solvent‐based protein crystals, and the rearrangement of molecules can be efficiently recorded in distinct diffraction patterns. This study focuses on this topic, reporting the effect of rH variation experiments on hen egg white lysozyme (HEWL) polycrystalline precipitates of tetragonal symmetry using X‐ray powder diffraction (XRPD). In situ XRPD data were collected on HEWL specimens during dehydration and rehydration processes using laboratory instrumentation. A known polymorph [space group P 43 21 2, a = 79.07181 (1), c = 38.0776 (1) Å] was identified during gradual dehydration from 95 to 63% rH and vice versa. Pawley analysis of collected data sets and accurate extraction of unit‐cell parameters indicated a characteristic evolution of the tetragonal axes with rH. In addition, there is a low humidity level below which samples do not retain their crystallinity. This work illustrates the accuracy of laboratory XRPD as a probe for time‐resolved studies of proteins and in situ investigations of gradual structural modifications upon rH variation. These experiments provide essential information for improving production and post‐production practices of microcrystalline protein‐based pharmaceuticals.